Simulering av Oorts moln och nära planeter - Strömbeck, Frida; Bore, Alexander; Rizk, Charbel; Ekdahl, Calle (My University, 2014)
Abstract To examine the influence of different surroundings on cometary orbits we used computer simulations. They showed that there are at least two different sources for the comets that make up the Oort cloud. They also showed that the galactic tide and star passages can send comets of the Oort cloud into the solar system. Comets inside the solar system were also simulated, to determine whether or not Jupiter could catch them, and also to examine which way to preferably avert a comet on a collision course towards Earth.
Keywords: Energi; Fysik; Astronomi, astrofysik och kosmologi; Energy; Physical Sciences; Astronomy, Astrophysics and Cosmology